SIMBIOSIS MUTUALISME PERPUSTAKAAN DENGAN MEDIA CETAK SEBAGAI UPAYA MEMBUDAYAKAN MEMBACA DAN MENULIS BAGI MASYARAKAT - Muhammad Rohmadi (Jurnal Pustaka Ilmiah, 2019)
Library and print media as a medium for the dissemination of information and knowledge resource centers. Both the media must have the positive integration of mutual benefi t. It is a form of strengthening the various models of information disseminated directly and indirectly. Various models of literacy and knowledge appeared in the print media and it is presented in the library. Therefore, it is necessary to unify the vision synergistic effort between the library and print media so that it can occur symbiotic mutualism between the library and the print media in a variety of contexts of science and technology and the arts.Key words: symbiotic mutualism, libraries, print media, reading, and writing.